Caracteristicas agronomicas de la produccion de raices y tuberculos: implicaciones para el diagnostico - Moreno, R.A. (International Center for Tropical Agriculture, 1989)
Important agronomic characteristics of common root and tuber crop production systems in the tropics are indicated for crops including cassava, yam, sweet potato, and edible aroids. Brief comments are also included on aspects that help correctly interpret the information obtained during the characterization process. The general context of agricultural production is analyzed, and within this context, the particular case of root crops, where the process of transformation into derived products, at both farm and regional levels, may condition the agronomic practices used. Energy input concentrated in 3 activities, namely land preparation, weed control, and harvesting and storage. The characterization process of production systems should be complemented with information on preparation of planting material, planting times, intercropping, and applications of chemicals. When characterizing a production system, the structure and operation of the production unit are important aspects as well as lot assignment, lot size, lot rotation, labor allocation, and use of capital and inputs. Important interactions occur between crop and animal production systems, annual and perennial crops, and perennial and food crops. Regional characteristics that also agronomically condition root crop production systems include land distribution, spatial distribution of production units, soil resources (fertility, topography), and climate. Steps to gather agronomic information are listed. (CIAT)